A new species of the genus Eryngiopus Summers (Acari: Stigmaeidae) from Hamedan Province, Iran - Mohammad Khanjani; Ladan Mohammadi; Alireza Nazari; Masoumeh Khanjani (Persian Journal of Acarology)
A new species of the genus Eryngiopus, E. hamedanicus Khanjani, Mohammadi & Nazari sp. nov. is described and illustrated based on females collected from soil under pear trees, Negarkhaton Village, Famenin town, Hamedan province, Iran.